Motion analysis of squash backhand drop shot - A kinematic analysis study - Kim, S. E.; Min, S. N.; Subramaniyam, M. (IOP Conf. Series: Materials Science and Engineering, 2018)
A hand-held sport characterises racket sports including squash, badminton, tennis, and ta le tennis. This study discusses squash and kinematics involved. There are varies shots can be played in squash including rail shot, boast shot, and backhand drop shot. Unlike other shots, the backhand drop shot requires control over the racket, control in swing speed and hitting angle, control in angular displacement of elbow, trunk and shoulder joints. With author`s knowledge, there were not much research studies on squash kinematics. This study considered squash backhand drop shot and performed the kinematic analysis. Subjects (squash players) in the twenties participated, who had no injuries in the last six months. The players were separated into expert and novice groups. The kinematic analysis was performed through a 3D motion analysis system when the players are performing backhand drop shot. The results compare the displacement and velocities of trunk and racket, and the angular displacements and velocities of elbow and shoulder joints between the groups. Statistical analysis was performed using SPSS 20.0. The lap time required by the expert group was longer than that of the novice group. The expert group was used significantly (p<0.001) lower racket speed than that of the other group. Also, the expert group was maintained significantly (p<0.001) more extended elbow joint angle after the shot. Similarly, the expert group only used elbow extension just before the shot. However, the novice group played with the pre-extended elbow joint. These results conclude that the racket should move fast during the down-swing period and move slowly during the followthrough period, and the shoulder joint should extend before the elbow joint extension for the efficient backhand drop shot in squash game.